Can sensory and semantic priming enhance the effects of guided self-compassion meditation? A proof-of-concept study - Buric, Ivana; Wrzesien, Maja; Milojičić, Jelica; Ridderinkhof, Anna; De Bruin, Esther; Bögels, Susan (Frontiers in Psychology, 2024)
Self-compassion is a fundamental aspect of psychological health and well-being that can be cultivated through self-compassion meditations, but it remains unclear how to facilitate this most effectively. This study is the first to explore whether sensory and semantic priming introduced prior to a guided self-compassion meditation could enhance the effects of meditation in comparison with a control condition. The study was conducted with 3x3 repeated measures between-group design, including three groups (sensory priming, semantic priming and control group), and three assessment time points of state self-compassion, self-criticism, and positive and negative affect (at baseline, after priming, and after guided meditation). Additionally, a meditation appeal questionnaire was used. The total sample size included 71 students who underwent a three-minute priming intervention followed by a 15-minute self-compassion guided meditation session. First, prior to guided meditation, sensory priming significantly decreased state self-criticism more than the control condition or semantic priming, although some reliability issues of the applied self-criticism scale must be taken into consideration. Second, neither sensory nor semantic priming changed state self-compassion, positive affect or negative affect. Third, neither semantic nor sensory priming significantly enhanced the effects of guided self-compassion meditation either in positive and negative affect, self-compassion states, self-criticism states, or in the appeal of the meditation experience. Although this study is underpowered (estimated post hoc power ranges from 0.20 to 0.42), the findings provide preliminary insights into the potential priming has as a tool to enhance meditation effects and provide guidelines for future studies.